2011
DOI: 10.1002/aic.12599
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced oxygen mobility and reactivity for ethanol steam reforming

Abstract: This article describes a strategy for increasing oxygen storage capacity (OSC) of ethanol steam reforming (ESR) catalysts. Sintering and carbon deposition are major defects of nickel-based catalysts for ESR; tuning oxygen mobility (OM) of CeO 2 -based supports can overcome these drawbacks and promote H 2 production. We have successfully increased OSC and OM by adding Mg into the lattice of Ni/CeO 2 to promote H 2 production in ESR. The insertion of Mg into the CeO 2 lattice efficiently promotes the reduction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 67 publications
5
47
0
1
Order By: Relevance
“…The oxygen storage capacity (OSC) was calculated based on oxygen uptake. These values allow us to estimate the total amount of oxygen available in the oxide catalyst (Zhang et al, 2012). The Co 20 /γ-Al 2 O 3 -CeO 2 catalyst has a larger OSC than the Co 10 /γ-Al 2 O 3 -CeO 2 catalyst, indicating that the former has a higher amount of oxygen vacancies, as also observed from the N 2 physisorption results.…”
Section: Characterization Of the Catalystsmentioning
confidence: 59%
“…The oxygen storage capacity (OSC) was calculated based on oxygen uptake. These values allow us to estimate the total amount of oxygen available in the oxide catalyst (Zhang et al, 2012). The Co 20 /γ-Al 2 O 3 -CeO 2 catalyst has a larger OSC than the Co 10 /γ-Al 2 O 3 -CeO 2 catalyst, indicating that the former has a higher amount of oxygen vacancies, as also observed from the N 2 physisorption results.…”
Section: Characterization Of the Catalystsmentioning
confidence: 59%
“…Ceria has been widely employed in several catalytic reactions, involving the WGS reaction [28], NOx reduction [29,30], oxidation or partial oxidation of hydrocarbons [31], steam reforming [32], etc., owing to its excellent redox properties. The mobile oxygen related to the ceria lattice, is considered to be responsible for the oxidation of deposited carbonaceous fragments, thus protecting the catalyst surface from poisoning [33][34][35][36]. In addition, mobile oxygen can activate water, with regard to the formation of hydroxyl groups, resulting in higher ESR efficiency [25,33].…”
Section: Introductionmentioning
confidence: 99%
“…The mobile oxygen related to the ceria lattice, is considered to be responsible for the oxidation of deposited carbonaceous fragments, thus protecting the catalyst surface from poisoning [33][34][35][36]. In addition, mobile oxygen can activate water, with regard to the formation of hydroxyl groups, resulting in higher ESR efficiency [25,33]. In a comprehensive study by Xu et al [25], utilizing both in situ and ex situ characterization techniques it was revealed that metallic Ni and Ce(III) entities were the active components under ESR conditions.…”
Section: Introductionmentioning
confidence: 99%
“…A high oxygen mobility (redox property), high oxygen storage capacity, strong interaction with the supported metal (strong metal-support interaction) and their ease of modification promoted several investigations of hydrogen production by SRE over CeO 2 supported catalysts [27][28][29]. Fajardo et al [30] performed SRE with S/EtOH of 3 at 673 K over Ni supported over CeO 2 catalyst prepared by using a biopolymer polymerization method.…”
Section: Catalytic Investigationsmentioning
confidence: 99%